Cathode Materials for Proton Exchange Membrane Fuel Cells: From Metal and Metal Composite Catalysts to Carbon‐Supported Hybrids in Oxygen Reduction Reaction - Claudia Garcés‐Barría; Daniel Cáceres‐Díaz; Javiera Torres‐Fernández; Tatiana M. Bustamante; Elizabeth Elgueta; Felipe Sanhueza (ChemElectroChem)
This review provides an overview of recent advancements in cathode materials for proton exchange membrane fuel cells (PEMFCs), focusing on their role in catalyzing the oxygen reduction reaction (ORR). This begins with a fundamental discussion of the ORR mechanism, including two‐electron and four‐electron pathways. The review then explores a wide range of electrocatalyst materials, starting with precious metal catalysts, particularly platinum‐based materials, along with alloying strategies and composite structures. This then delves into nonprecious metal catalysts, encompassing metal‐free ORR electrocatalysts, carbon‐supported composite materials (including heteroatom doping and metal‐carbon composites), and transition metal oxides. The review further examines metal phthalocyanines, biomass‐derived catalysts, bimetallic and trimetallic nanoparticles supported on carbon matrices, and chalcogenides (oxides, sulfides, and selenides) as ORR electrocatalysts. Advanced materials such as single‐ and dual‐atom catalysts, high‐entropy alloys, and metal organic frameworks derived electrocatalysts are also discussed. We analyze the identification of reaction sites and the effect of structure on catalytic activity. Furthermore, the review covers electrochemical measurements in PEMFCs and explores technological applications and industrial relevance, including products and patents. Finally, this review concludes by addressing future perspectives and challenges in the field of cathode materials for PEMFCs.